Identificación de alcaloides por métodos espectrométricos y espectroscópicos aislados de la raíz de Tabernaemontana markgrafiana J.F. Macbr. uchu sanango recolectado en Mazán 2020 - Insapillo Fatama, Elvis Cristian (2024)
The purpose of this research study was to isolate and describe the structural characteristics of the alkaloids present in the roots of the plant Tabernaemontana markgrafiana J.K. Macbr (known as Uchu sanango) using spectroscopic and spectrometric methods. To carry out the process, the root of Tabernaemontana markgrafiana J.K. Macbr. (2,100 kg) was dried at a temperature of 20 °C for 15 days. Subsequently, an ethanolic extraction was performed by maceration with ethanol for 30 days, changing the solvent every 48 hours. The ethanol was removed by reduced pressure in a rotary evaporator until a dry extract with a weight of 138,20 g was obtained. From the ethanolic extract (138,20 g), different fractions were obtained: an acidic alkaloidal extract (3,34 g), an acidic alkaloidal residue (58,26 g), a basic alkaloidal extract (593,3 mg), and a basic alkaloidal residue (6,23 g). In conclusion, chromatographic techniques were performed to separate the alkaloidal extracts, and the chemical structure of three alkaloids was determined: Voacristine, Voacangine hydroxyindolenine, and 19 S Heyneanine. The chemical structure of these compounds was determined by interpreting spectrometric (MS) and spectroscopic (1H NMR and 13C NMR) data and compared with information published in the scientific literature on chemistry.